Synthesis and Characterization of a Series of Chromone–Hydrazones - I. Hamzi (Chemistry Proceedings)
Chromones, a class of aromatic heterocyclic compounds, possess intriguing biological and optical properties, making them ideal for spectroscopic detection. Hydrazones, known for their chelating abilities, can selectively bind to metal ions. This study presents a series of novel chromone–hydrazone derivatives synthesized from 3-formylchromone and three different hydrazine compounds. The structures of these synthesized compounds were confirmed through spectral analysis using 1H NMR, 13C NMR, and FT-IR spectroscopy.